Improving profitability through green manufacturing : creating a profitable and environmentally compliant manufacturing facility - Hillis, David R. (Wiley, 2013)
Manufacturers can be green and highly profitable at the same time. Profits do not have to be sacrificed to environmental responsibility, or vice versa. Following this book's tested and proven approach, readers discover how to create and operate manufacturing facilities that are highly profitable while meeting or exceeding the environmental standards of their local community, state, and federal governments. The authors' approach is broad in scope, setting forth the roles and responsibilities of organizational functions such as marketing, product design, manufacturing technology, management, and human resources. The book begins with an overview explaining why profitability and green manufacturing must be viewed as a single objective. Next, the book becomes a "how to" guide to creating and maintaining an environmentally compliant and profitable manufacturing operation, with chapters covering: * Manufacturing, waste, and regeneration * Building a decision-making model * Environmental regulation, standards, and profitability * Case studies * Tools used to improve manufacturing operations * The facility * Applying the profitable and compliant process chart. The final chapter is dedicated to a step-by-step approach in the application and use of the profitable and compliant process chart, a core working tool discussed in the book. In this chapter, several actual manufacturing applications, along with their worksheets, are presented to illustrate how this approach can minimize resources and waste. Armed with this comprehensive systems approach, readers will no longer view profitability and green manufacturing as two opposing goals. Instead, they'll have the tools and knowledge needed to create and maintain a manufacturing operation that is both profitable and green.